2011
DOI: 10.1074/jbc.m110.206813
|View full text |Cite
|
Sign up to set email alerts
|

A Spring-loaded Release Mechanism Regulates Domain Movement and Catalysis in Phosphoglycerate Kinase

Abstract: Phosphoglycerate kinase (PGK) is the enzyme responsible for the first ATP-generating step of glycolysis and has been implicated extensively in oncogenesis and its development. Solution small angle x-ray scattering (SAXS) data, in combination with crystal structures of the enzyme in complex with substrate and product analogues, reveal a new conformation for the resting state of the enzyme and demonstrate the role of substrate binding in the preparation of the enzyme for domain closure. Comparison of the x-ray s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(115 citation statements)
references
References 42 publications
8
105
1
1
Order By: Relevance
“…alaska) chloroplast photosystem I (PSI) were kindly provided by Prof. Nathan Nelson (Department of Molecular Biology and Biochemistry, Tel Aviv University, Israel). Crystals of human phosphoglycerate kinase (hsPGK) were grown as previously described Zerrad et al, 2011). Crystals of L. lactis b-phosphoglucomutase (bPGM) were grown as described .…”
Section: Methods For Examplesmentioning
confidence: 99%
“…alaska) chloroplast photosystem I (PSI) were kindly provided by Prof. Nathan Nelson (Department of Molecular Biology and Biochemistry, Tel Aviv University, Israel). Crystals of human phosphoglycerate kinase (hsPGK) were grown as previously described Zerrad et al, 2011). Crystals of L. lactis b-phosphoglucomutase (bPGM) were grown as described .…”
Section: Methods For Examplesmentioning
confidence: 99%
“…It has been demonstrated that the enzyme remains mostly in an open conformation, with short bursts of closure for catalysis. 17 In this situation, an enhanced mechanism for substrate and product exchange has clear advantages.…”
Section: Conclusion: Causes and Implications Of Substrate Antagonismmentioning
confidence: 99%
“…For phosphotransfer to be allowed, upon the binding of both substrates, an extensive hinge bending motion occurs that leads to a "closed" conformation, resulting in amalgamation of the sites. 16,17 While extensive structural studies have been carried out on the open form of PGKs from a number of sources (Kovári and Vas 18 and references cited therein), the first structure of a closed form was, until recently (see the text below), obtained only for the enzymes from Trypanosoma brucei (the causative agent of sleeping sickness) 19 and Thermotoga maritima. 20 In these works, it was shown that, in the ternary PGK·PG·ADP complex, there was a dramatic closing of the large cleft that separates the two substrate sites, thereby bringing bound PG and ADP in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis was performed using the model of the reduced protein and imposing the formation of the disulfide bond between Cys 227 and Cys 361 by energy minimization to adjust the protein conformation. It has been demonstrated for human PGK that after binding of the two substrates, the enzyme assumes a half-closed conformation in which the two substrates appear too distant from each other to allow phosphoryl transfer (28). A significant "hinge bending" movement, which leads the enzyme to a closed conformation, was suggested to allow enzyme catalysis to occur.…”
Section: Conditionsmentioning
confidence: 99%
“…The N-terminal domain contains the 3-PGA binding site, whereas the ATP cofactor binds to the C-terminal domain. After substrate binding, a conformational change brings the two domains in close proximity, generating the so-called "closed conformation" that ensures catalytic reactions (28).…”
mentioning
confidence: 99%